Defining the ABC of gene essentiality in streptococci - Charbonneau, Amelia R. L.; Forman, Oliver P.; Cain, Amy K.; Newland, Graham; Robinson, Carl; Boursnell, Mike; Parkhill, Julian; Leigh, James A.; Maskell, Duncan J.; Waller, Andrew S. (BioMed Central, 2017)
Background: Utilising next generation sequencing to interrogate saturated bacterial mutant libraries provides unprecedented information for the assignment of genome-wide gene essentiality. Exposure of saturated mutant libraries to specific conditions and subsequent sequencing can be exploited to uncover gene essentiality relevant to the condition. Here we present a barcoded transposon directed insertion-site sequencing (TraDIS) system to define an essential gene list for Streptococcus equi subsp. equi, the causative agent of strangles in horses, for the first time. The gene essentiality data for this group C Streptococcus was compared to that of group A and B streptococci.